2015
DOI: 10.1590/s1519-38292015000400009
|View full text |Cite
|
Sign up to set email alerts
|

Advanced malignant melanoma during pregnancy: technical description of sentinel lymph node biopsy followed by radical lymph node dissection

Abstract: Introduction: melanoma is a very aggressive cancer, with increasing incidence, and is currently the fifth most common cancer in men and the sixth most common in women in the United States. Melanoma is not unusual in pregnancy, with an estimated occur-rence rate of 1:1.000. Although not the most common cancer in pregnancy, melanoma is the tumor with the highest incidence ofplacenta and fetus metastases. Description: a 29-year-old lady, 4 weeks after conception underwent resection of an atypical pigmented les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…MB, used in the present study, was chosen due to some characteristics, such as easy acquisition, low cost, and safe use in dogs. No reactions to MB, like the hypersensitivity described in other studies (REESE et al, 2016;SOUZA et al, 2016;SUAMI et al, 2008;SUAMI et al, 2013;SUAMI et al, 2016;SUGA et al, 2007;WAINSTEIN et al, 2015), were observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…MB, used in the present study, was chosen due to some characteristics, such as easy acquisition, low cost, and safe use in dogs. No reactions to MB, like the hypersensitivity described in other studies (REESE et al, 2016;SOUZA et al, 2016;SUAMI et al, 2008;SUAMI et al, 2013;SUAMI et al, 2016;SUGA et al, 2007;WAINSTEIN et al, 2015), were observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…Essas deformações cutâneas podem ser atribuídas à influência hormonal do estrogênio, da progesterona e do hormônio estimulante dos melanócitos (MSH), resultando na maior ocorrência de alterações de grande importância clínica, que vão desde o surgimento de melasma até casos mais graves, como o desenvolvimento de melanoma, a partir de nevos melanocíticos. Apesar deste tipo de câncer não ser o mais comum na gestação, apresenta alto índice de metástases da placenta e do feto, o que geralmente não é considerado em Obstetrícia [5,6,[11][12][13].…”
Section: Discussionunclassified
“…Embora se trate de uma região de clima quente e índice elevado de radiação solar, o melasma está associado a outros fatores além dos climáticos, entre eles, predisposição genética, fatores hormonais e estilo de vida. Este último inclui a importância da prática correta de fotoproteção e o uso diário de protetor solar com FPS igual ou superior a 30 é, ainda, um dos meios mais efetivos de prevenção da hiperpigmentação durante a gestação [3,12,17,23,24].…”
Section: Discussionunclassified
“…As for human prostate cancer, pelvic lymphadenectomy is considered the most accurate staging procedure, being suggested in some studies this therapeutic alternative, but still with inconsistent data [2,4,17]. In animals, there are no studies on the therapeutic feasibility of lymphadenectomy, which is believed to be palliative in the reported patient, owing to the fact that it is a tubulopapillary carcinoma with different foci of lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%